Quality of life evaluation of coinfected patients with HIV/tuberculosis in a hospital in northeast Brazil - Amanda D. SILVA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objectives: To evaluate the quality of life of patients coinfected with HIV/tuberculosis and to understand their perception of their health. Methods: A cross-sectional study was carried out in a hospital in the state of Pernambuco, Brazil. Data were collected between November 2017 and April 2018 through interviews. The WHOQOL-HIV Bref instrument was used, obtaining the total score and performance in the domains: physical, psychological, level of independence, social relationships, environment, spirituality. Sociodemographic and clinical data from the Logistic Control System of Medicines (SICLOM®) were also collected through a questionnaire. Results: Twenty-six patients were interviewed, 76.9% were male, mostly heterosexual, single, 43.1% presented an advanced state of immune system compromise. 73.1% considered their health "good" or "very good" and 69.2% did not consider themselves sick. The general quality of life, score from zero (worst quality of life) to one hundred (best quality of life) obtained an average of 69.6 ± 9.1. In the domains, the worst average was obtained at the independence level (11.1 ± 2.6) and the highest scores were in the spirituality (15.5 ± 3.8) and psychological (15.3 ± 2.2) domains. Conclusions: The low level of independence and the unfavorable socioeconomic conditions were important aspects influencing in the quality of life of the studied population. Knowledge about the most affected domains in the quality of life allows the elaboration of clinical guidelines and public assistance policies that contribute to the well-being of these patients.